2023
DOI: 10.32568/jfce.1296134
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Emotion Regulation in the Relationship between Self-Compassion and Subjective Well-Being in School in Secondary School Students

Lokman KOÇAK,
Elif TERZİ

Abstract: This study focuses on the mediating role of emotion regulation in the relationship between self-compassion and subjective well-being in school in secondary school students. The Brief Adolescents’ Subjective Well-Being in School Scale, Self-Compassion Scale for Adolescents and Emotion Regulation Scale for Adolescents were administered to a sample of 415 adolescents (48.9% females and 51.1% ma-les). The data was analysed with correlation analysis and regression-based mediation analysis to inves-tigate the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The results of the study concluded that emotion regulation -cognitive appraisal partially mediates the role of self-compassion on depressive symptoms in adolescents. The results of the next study by Koçak and Terzi (2023), who examined the role of emotion regulation in the relationship between self-compassion and subjective well-being in junior high school students, where the role of mediating regulation is also partial. Research on this topic can extend the literature on the role of self-compassion on mental health through emotion regulation as a mediator.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study concluded that emotion regulation -cognitive appraisal partially mediates the role of self-compassion on depressive symptoms in adolescents. The results of the next study by Koçak and Terzi (2023), who examined the role of emotion regulation in the relationship between self-compassion and subjective well-being in junior high school students, where the role of mediating regulation is also partial. Research on this topic can extend the literature on the role of self-compassion on mental health through emotion regulation as a mediator.…”
Section: Discussionmentioning
confidence: 99%